Психолінгвістичні універсалії розуміння молитви "Отче наш" (дискурсивний підхід) - Савелюк, Наталія (Lesya Ukrainka Eastern European National University, 2017)
The author grounds empirically and theoretically a discursive approach to the study of the features of comprehending a prayer as a basic genre of religious discourse. Religious discourse is viewed as an active reception, transmission and/or creation (co-creation) of religious texts in their specific contexts (broad social, including communicative and individual settings). It is associated with the construction of religiously relevant discursive models of reality and its components in accordance with respectively oriented concepts and utterances (statements). Therefore, selection, formulation of such utterances and their comprehension are treated as the consequence of the appropriate active choices of the subject of religious discourse (individual or collective). In this regard, it is substantiated that a prayer includes not only the system of its generalized, traditional meanings (theological and linguistic levels of analysis), but also individual, contextually conditioned perception and comprehension by its specific subject (psychological and psycholinguistic levels of analysis). The conceptual basis of the empirical research is the discursive approach. The methodical basis is psycholinguistic text analysis. The fundamental methods and techniques are “The measuring technique of religious activity” by D.O. Smirnov and the content analysis of the recorded religious discourses. Due to the analysis of the canonical prayer “Our Father” and the forthcoming religious discourses (products of its comprehension) of the respondents with different levels of religious activity (low, below average, above average, high), the author defines basic categories through which the comprehension of such discourse takes place: 1) “Being and its common attributes”; 2) “God, His name and attributes”; 3) “A Person and his/her everyday existence”; 4) “Prayer and its components”; 5) “Good (spiritual)”; 6) “Forbidden (sinful)”. The following general trends (from the lowest to the highest levels of religious activity) are also stated: significant increase (the amount of words, the amount of sentences and the average amount of words in a sentence), insignificant increase (indicators of emotional intensity) and decrease (indicators of lexical diversity and lexical density of religious discourses of Ukrainians). У статті теоретично та емпірично обґрунтовується дискурсивний підхід до дослідження особливостей розуміння молитви як базового жанру релігійного дискурсу. Релігійний дискурс розглядається як активна рецепція, передавання та/або творення (співтворення) релігійних текстів у певних їх контекстах (широких соціальних, зокрема, комунікативних, а також індивідуальних життєвих ситуаціях), що пов’язане з конструюванням релігійно релевантних дискурсивних моделей реальності та її складових через сукупність відповідно зорієнтованих понять і висловлювань (тверджень). У свою чергу, підбір, формулювання таких висловлювань, а також їх розуміння розглядаються як наслідок відповідних активних виборів суб’єкта релігійного дискурсу (індивідуального або колективного). У зв’язку з цим обґрунтовується, що молитва включає у себе, поряд із системою узагальнених, традиційних своїх значень (теологічний та лінгвістичний рівні аналізу), також індивідуальне, контекстуально зумовлене сприйняття та осмислення конкретним своїм суб’єктом (психологічний та психолінгвістичний рівні аналізу). На прикладі канонічної молитви «Отче наш» та зустрічних релігійних дискурсів (продуктів її розуміння) респондентів із різними рівнями релігійної активності (низьким, нижчим за середній, вищим за середній, високим) виокремлено базові категорії, крізь призму яких відбувається розуміння молитовного дискурсу: 1) «Буття та його загальні атрибути»; 2) «Бог, Його ім’я та атрибути»; 3) «Людина та її повсякденне буття»; 4) «Молитва та її складові»; 5) «Належне (духовне)»; 6) «Заборонене (гріховне)». Також констатовано наступні загальні тенденції (від найнижчого до найвищого рівня релігійної активності): істотне зростання – кількості слів, кількості речень і середньої кількості слів у реченні, слабке зростання – показників емоційної напруженості, а спадання – показників лексичної різноманітності та лексичної щільності релігійних дискурсів досліджених українців.
Keywords: discursive approach; religious activity; religious discourse; prayer; comprehension; categories; lexemes; дискурсивний підхід; релігійна активність; релігійний дискурс; молитва; розуміння; категорії; лексеми